Coated metal foil and metal-clad laminate
The metal foil with a coating layer, featuring specific XPS ratios and plasma polymer characteristics, addresses the issue of decreased adhesion at high temperatures, ensuring robust adhesion and durability for printed wiring boards.
Patent Information
- Application Number
- JP2024565142
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-08-04
- Filing Date
- 2024-07-23
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-07-23
AI Technical Summary
Existing metal foils with surface roughening and silane coupling agent treatments experience decreased adhesion with insulating substrates when exposed to high-temperature environments, leading to potential transmission losses and durability issues in printed wiring boards.
A metal foil with a coating layer having a thickness of 5 to 1000 nm, where the C1s spectrum by X-ray photoelectron spectroscopy shows a ratio of peak area derived from C-O bonds to total peak area of 10-50%, and the coating layer contains a plasma polymer with specific atomic concentrations and bond strengths, enhancing adhesion and heat resistance.
The metal foil with a coating layer exhibits excellent adhesion with other materials and maintains this adhesion even at high temperatures, ensuring reliable performance in harsh environments for printed wiring boards.
Smart Images

Figure 0007654911000002 
Figure 0007654911000003 
Figure 0007654911000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a coated metal foil and a metal-clad laminate. [Background technology]
[0002] In recent years, with the advancement of high performance and functionality in information and communication devices and the development of networks, there is a need to transmit and process large volumes of information at higher speeds. As a result, the signals being transmitted tend to be of increasingly higher frequency, and there is a demand for printed wiring boards that suppress the transmission loss of high-frequency signals.
[0003] In the manufacture of printed wiring boards, a metal foil such as copper foil is usually laminated with an insulating substrate (resin substrate), and then heated and pressed to form a metal-clad laminate to form a conductor circuit. In order to increase the adhesion between the insulating substrate and the metal foil, the metal foil surface has been conventionally roughened by electroplating or etching, and the adhesion between the insulating substrate and the metal foil is increased by a physical action (anchor effect). However, when the skin effect phenomenon becomes evident due to the increase in the frequency of signals, the transmission path becomes longer on the roughened surface, resulting in large transmission losses.
[0004] The metal foil surface is roughened and then treated with a silane coupling agent to enhance the chemical adhesion to the resin substrate. For example, Patent Document 1 describes a surface-treated copper foil for printed wiring boards having a silane coupling agent layer on the surface on which roughening particles are formed, the average height of the roughening particles on the surface of the silane coupling agent layer being 0.05 μm or more and less than 0.5 μm, and the BET surface area ratio of the surface of the silane coupling agent layer being 1.2 or more. It is said that by using the surface-treated copper foil described in Patent Document 1, a printed wiring board can be obtained that highly suppresses transmission loss even when transmitting high-frequency signals in the GHz band, has high adhesion between the copper foil and the resin substrate even at high temperatures, has excellent durability under harsh conditions, and is less likely to short-circuit.
[0005] A technique using plasma discharge is known as a coating technique for substrates. For example, it has been proposed to apply a coating to a substrate by plasma polymerization of a gas containing an organic compound or monomer in order to impart corrosion resistance and oxidation resistance to the substrate, to improve adhesion to other materials, and to increase surface activity. For example, Patent Document 2 describes a method for forming a coating on a substrate, which includes introducing a sprayed liquid and / or solid coating-forming material into an atmospheric pressure plasma discharge and / or an ionized gas flow generated therefrom, and exposing the substrate to the sprayed coating-forming material. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2017-106068 A [Patent Document 2] Special Publication No. 2004-510571 Summary of the Invention [Problem to be solved by the invention]
[0007] As a result of repeated investigations, the present inventors have found that in the production of a metal-clad laminate, even when the roughening of the metal foil surface and the formation of a silane coupling agent layer are combined as described in the above Patent Document 1, the adhesion between the metal foil and the insulating substrate is likely to decrease when the obtained metal-clad laminate is exposed to a severe high-temperature environment. Recently, printed wiring boards are sometimes exposed to temperatures of about 100 to 300°C during the manufacturing process or in the usage environment, and there is a demand for further improvement in heat resistance with respect to the adhesion between the metal foil and the insulating substrate.
[0008] An object of the present invention is to provide a metal foil that has excellent adhesion to other materials and can sufficiently maintain this adhesion even at high temperatures, and a metal-clad laminate obtained by laminating the metal foil and an insulating base material. [Means for solving the problem]
[0009] The above object of the present invention is achieved by the following means. [1] A coated metal foil, The coating layer has a thickness of 5 to 1000 nm, and in a C1s spectrum by X-ray photoelectron spectroscopy, the ratio of a peak area derived from a C-O bond to a total area of peaks derived from each bond detected at 280 to 292 eV (R C-O ) is 10 to 50%. [2] The metal foil with a coated layer according to [1], wherein the total atomic concentration (at%) of silicon, aluminum, titanium and sulfur in the coating layer is 0.5 times or more the carbon atom concentration (at%). [3] The metal foil with a coated layer according to [1] or [2], wherein the coating layer has a silicon atom concentration of 8 at % or more. [4] The metal foil with a coating layer according to any one of [1] to [3], wherein the coating layer satisfies the ratio [O-Si-O bond strength] / [C-Si-O bond strength]≧1 in a Si2p spectrum by X-ray photoelectron spectroscopy. [5] The ratio (R C-O ) is 10 to 45%. [6] The coating layer has a thickness of 30 to 990 nm and a ratio (R C-O ) is 13 to 30%, and 26≧[O—Si—O bond strength] / [C—Si—O bond strength]≧10 is satisfied. [7] The coated metal foil according to any one of [1] to [6], wherein the metal foil is a copper foil. [8] The metal foil with a coating layer according to any one of [1] to [7], wherein the coating layer contains a plasma polymer. [9] A metal-clad laminate obtained by laminating an insulating substrate and the coated metal foil according to any one of [1] to [8], with the coating layer of the coated metal foil facing the insulating substrate.
[0010] In the present invention, a numerical range expressed using "to" means a range including the numerical values before and after "to" as the lower and upper limits. Effect of the Invention
[0011] The coated metal foil of the present invention has excellent adhesion to other materials and can adequately maintain this adhesion even at high temperatures. Also, the metal-clad laminate of the present invention can adequately maintain adhesion between the insulating substrate and the metal foil even at high temperatures. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is an explanatory diagram that shows a schematic configuration example of a plasma polymerization apparatus for forming a coating layer on a metal foil surface. [Diagram 2] 2 is a SEM image of one embodiment of the coated metal foil of the present invention, where (I) is a photograph of the coated metal foil taken from the coating layer side, and (II) is a cross-sectional photograph of the coated metal foil. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Preferred embodiments of the present invention are described below.
[0014] [Coated metal foil] The coated metal foil of the present invention has a coating layer with a thickness of 5 to 1000 nm, that is, a coating layer thicker than a conventional surface treatment layer (about 2 to 3 nm) using a silane coupling agent. In addition, the coating layer has a ratio of the peak area derived from the CO bond to the total area of the peaks derived from the bonds detected at 280 to 292 eV in the C1s spectrum by X-ray photoelectron spectroscopy (XPS) (R C-O ) is between 10 and 50%. In the coated metal foil of the present invention, the coating layer may be provided on one side or both sides of the metal foil depending on the purpose.
[0015] <Coat layer> From the viewpoint of adhesion when laminated with other materials and high temperature durability, the thickness of the coating layer is preferably 7 to 1000 nm, more preferably 10 to 1000 nm, even more preferably 15 to 1000 nm, even more preferably 18 to 1000 nm, even more preferably 20 to 1000 nm, even more preferably 30 to 990 nm, even more preferably 35 to 960 nm, even more preferably 40 to 940 nm, and even more preferably 45 to 920 nm. In the present invention, the thickness of the coating layer is determined by exposing a cross section in the thickness direction of the metal foil with the coating layer by ion milling and observing the cross section with a high-resolution scanning electron microscope (HR-SEM). The thickness is measured at one random location in the SEM image of the cross section, and then at locations shifted 1 μm and 2 μm from the random location in the direction perpendicular to the thickness (horizontal direction), and the arithmetic average value of the thicknesses at the three locations in total is taken as the thickness of the coating layer.
[0016] The above coating layer is formed by adjusting the above ratio (R C-O ) is preferably 10 to 45%, more preferably 12 to 40%, even more preferably 12 to 35%, still more preferably 13 to 30%, even more preferably 13 to 28%, and still more preferably 14 to 24%. The above XPS analysis is an XPS analysis of the surface of the coating layer. In the C1s spectrum of the XPS analysis, peaks derived from each of the bonds O-C (=O)-O bond (peak top is about 290 eV), O-C=O bond (peak top is about 289 eV), C=O bond (peak top is about 288 eV), C-O bond (peak top is about 286 eV), C-C bond (peak top is about 285 eV), and C-H bond (peak top is about 285 eV) are detected within the range of 280 to 292 eV. Therefore, the above ratio (R C-O) means the ratio of the peak area derived from a C-O bond to the sum of the areas of the peaks derived from an O-C(=O)-O bond, an O-C=O bond, a C=O bond, a C-O bond, a C-C bond, a C-C bond, and a C-H bond (total area of the peaks). In the present invention, the XPS analysis of the surface of the coating layer is performed by randomly analyzing five points on the surface of the coating layer. A C1s spectrum is obtained by XPS for each of the five points, and the ratio (%) of the peak area derived from the C-O bond to the total area of each peak derived from each bond detected at 280 to 292 eV is calculated for each of the five points, and the arithmetic average of the calculated values obtained for each of the five points is taken as the ratio (R C-O Specific measurement conditions for the XPS analysis will be described in the Examples section below.
[0017] From the viewpoint of adhesion when laminated with other materials and high-temperature durability, the coating layer preferably has a total atomic concentration (at %) of silicon, aluminum, titanium and sulfur in the coating layer that is 0.5 times or more, more preferably 0.5 to 3.0 times, even more preferably 0.5 to 2.5 times, even more preferably 0.5 to 2.2 times, and even more preferably 0.6 to 2.0 times, of the carbon atom concentration (at %) in the coating layer. The silicon atom concentration in the coating layer is preferably 8 at % or more, more preferably 10 to 30 at %, further preferably 10 to 20 at %, and even more preferably 12 to 20 at %. The above atomic concentrations are determined by subjecting the surface of the coating layer to XPS analysis, and taking the arithmetic average of five measured values for each atomic concentration.
[0018] From the viewpoint of adhesion when laminated with other materials and its high temperature durability, the above coating layer is determined as follows in the Si2p spectrum of XPS analysis: [O-Si-O bond strength] / [C-Si-O bond strength]≧1 It is preferable that 40≧[O-Si―O bond strength] / [C-Si―O bond strength]≧2 It is more preferable that 30≧[O-Si―O bond strength] / [C-Si―O bond strength]≧4 It is more preferable that 28≧[O-Si―O bond strength] / [C-Si―O bond strength]≧6 It is more preferable that 27≧[O-Si―O bond strength] / [C-Si―O bond strength]≧8 It is more preferable that 26≧[O-Si―O bond strength] / [C-Si―O bond strength]≧10 It is more preferable that 25≧[O-Si―O bond strength] / [C-Si―O bond strength]≧12 It is more preferable that 24≧[O-Si―O bond strength] / [C-Si―O bond strength]≧13 It is more preferable that the following condition is satisfied.
[0019] The XPS analysis for determining [O-Si-O bond strength] / [C-Si-O bond strength] is an XPS analysis of the surface of the coating layer. In the Si2p spectrum of the XPS analysis, the peak area derived from the O-Si-O bond and the peak area derived from the C-Si-O bond detected at 96 to 110 eV are determined, and [peak area derived from the O-Si-O bond] / [peak area derived from the C-Si-O bond] is calculated. The calculated value obtained is [O-Si-O bond strength] / [C-Si-O bond strength]. The XPS analysis of the surface of the coating layer is carried out by randomly analyzing five points on the surface of the coating layer. An Si2p spectrum is obtained by XPS for each of the five points, and [O-Si-O bond strength] / [C-Si-O bond strength] is calculated for each of the five points. The arithmetic average of the calculated values for each of the five points is defined as the [O-Si-O bond strength] / [C-Si-O bond strength] defined in the present invention. The specific measurement conditions for the XPS analysis are described in the examples below.
[0020] The method for forming the coating layer is not particularly limited as long as the coating layer defined in the present invention can be formed. For example, it can be formed by plasma polymerization. That is, in one embodiment of the coating layer, the coating layer contains a plasma polymer. The formation of the coating layer on the surface of the metal foil by plasma polymerization is performed by generating plasma by high frequency waves, fragmenting the raw material (monomer) by the plasma and activating it at the same time, and the activated fragmented raw material reacts and polymerizes to form a plasma polymer film on the surface of the metal foil. In the plasma polymer, the raw material is fragmented and activated, and then a polymerization reaction occurs randomly, so that various chemical structures such as linear, branched, cyclic, and crosslinked are formed. The plasma polymerization technology itself is known.
[0021] The plasma polymerization is preferably atmospheric pressure plasma polymerization. By adopting atmospheric pressure plasma polymerization, oxygen can be more easily incorporated into the obtained plasma polymer than in low pressure plasma polymerization using a vacuum chamber. As a result, the ratio (R C-O ) to 10% or more. In addition, by controlling the selection of the raw material for plasma polymerization, the plasma exposure time of the raw material (the time during which the raw material is fragmented (activated) by contact with the plasma, also called the decomposition reaction time), and the contact time of the fragmented (activated) raw material with the metal foil surface (the time during which a polymerization reaction occurs on or near the substrate surface (polymerization reaction time)), the ratio (R C-O ) can be controlled to a range of 10 to 50% or to a more limited range.
[0022] The raw materials in the plasma polymerization are not particularly limited as long as the coating layer defined in the present invention can be obtained. Preferable examples of the raw materials include organic solvents (lower alcohols such as ethanol, methanol, and 2-propanol), metal alkoxide compounds, etc., which can be used alone or in combination of two or more. Examples of the metal alkoxide compounds include silicon alkoxide compounds (silane coupling agents), titanium alkoxide compounds (titanate coupling agents), aluminum alkoxide compounds (aluminate coupling agents), zirconium alkoxide compounds (zirconate coupling agents), etc., and metal alkoxide compounds selected from silicon alkoxide compounds, titanium alkoxide compounds, and aluminum alkoxide compounds are preferred, and silicon alkoxide compounds are more preferred. The metal alkoxide compounds can contain sulfur atoms, phosphorus atoms, etc. The molecular weight of the raw materials is preferably 100 to 300. Among them, it is preferable to use a combination of an organic solvent and a silicon alkoxide compound as the raw material. In this case, it is preferable to use, for example, an alcohol (for example, a lower alcohol having 1 to 3 carbon atoms) as the organic solvent.
[0023] As the carrier gas in the plasma polymerization, it is preferable to appropriately use an inert gas such as argon, nitrogen, or helium. The above-mentioned raw materials are supplied by volatilizing and mixing with the carrier gas, or dispersing in the carrier gas by bubbling or the like. The temperature of the raw materials or carrier gas is appropriately controlled according to the film formation rate, etc. For example, when a silane coupling agent is used as the raw material, it can be controlled to about 40 to 90°C.
[0024] FIG. 1 is a diagram showing a schematic configuration example of a plasma polymerization reaction apparatus applicable to the formation of a coating layer in the present invention. By passing an AC current between the planar electrodes 4, the carrier gas CG is turned into plasma between the planar electrodes 4, and the raw material supplied from the raw material supply device 3 to the planar electrodes 4 is fragmented (activated) by the action of this plasma. By exposing the surface of the metal foil to this fragmented activated raw material 5, plasma polymer is deposited on the surface of the metal foil to form a coating layer. In FIG. 1, the matching box 2 plays a role in adjusting the impedance so that the reflected wave is minimized for the applied high-frequency output.
[0025] The frequency of the AC current flowing between the planar electrodes 4 is not particularly limited as long as it generates the desired plasma gas. For example, it can be 1 kHz to 27.12 MHz. The output of the AC current is also not particularly limited as long as it generates the desired plasma gas. For example, it can be about 10 to 500 W, and preferably about 50 to 200 W. Copper, aluminum, etc. may be used for the planar electrodes 4. Also, a dielectric material such as glass may be attached to the electrode surfaces facing each other.
[0026] <Metal foil> The type of metal foil in the coated metal foil of the present invention is not particularly limited and can be appropriately selected according to the purpose. This metal foil may be an alloy consisting of two or more metals. For example, when the coated metal foil of the present invention is used in a metal-clad laminate of a printed wiring board, the metal foil can be a copper foil. In addition to being used in a metal-clad laminate, the coated metal foil of the present invention can be used as, for example, an aluminum foil, an aluminum plate, a Ni-plated foil, a Sn-plated foil, etc. The thickness of the metal foil with the coating layer is not particularly limited and is appropriately set according to the purpose. For example, the thickness including the coating layer is preferably 0.03 to 3 mm, more preferably 0.03 to 0.5 mm. The thickness of the metal foil with the coating layer can be determined in the same manner as the thickness of the coating layer described above.
[0027] [Metal-clad laminate] The metal foil with a coating layer of the present invention can be suitably used as the metal foil of a metal-clad laminate used for a printed wiring board. By laminating the metal foil with a coating layer of the present invention and an insulating substrate (resin substrate), and heating and pressing this by a conventional method to bond them, a metal-clad laminate can be obtained. The lamination of the metal foil with a coating layer of the present invention and the insulating substrate is preferably in a form where the coating layer side of the metal foil with a coating layer is laminated on the insulating substrate side. When the metal foil with a coating layer of the present invention has coating layers on both sides, either side can face the insulating substrate side. The metal foil with a coating layer of the present invention applied to a metal-clad laminate can be a copper foil with a coating layer, an aluminum foil with a coating layer, a Ni-plated foil with a coating layer, a Sn-plated foil with a coating layer, etc., and a copper foil with a coating layer is preferred.
Examples
[0028] [Analysis method] <Thickness of the coating layer> Using IM4000 manufactured by Hitachi, Ltd., the cross-section in the thickness direction of the metal foil with a coating layer was exposed by ion milling. For this cross-section, an SEM image was obtained at an acceleration voltage of 3 kV using HR-SEM (product name: SU8020) manufactured by Hitachi, Ltd. Regarding this SEM image, the thickness of the coating layer was measured at three locations as described above, and the arithmetic mean value of the three measured values was taken as the thickness (nm) of the above coating layer.
[0029] <Ratio (R of the peak area derived from the C-O bond C-O )> Surface analysis by XPS was performed on the surface of the coating layer of the metal foil with a coating layer using PHI Quantes manufactured by ULVAC-PHI, Inc. The excitation X-ray was a monochromatized Al-Kα ray (1486.6 eV), and the measurement was performed with an escape angle of 45° and an analysis region of 100 μmφ. The C1s spectrum with a binding energy of 280 to 292 eV was peak-fitted to separate the spectral components. The ratio (R of the peak area derived from the C-O bond to the total area of each peak (the total area of each peak) derived from each bond of the O-C(=O)-O bond, O-C=O bond, C=O bond, C-O bond, C-C bond, and C-H bond C-O) was determined. The ratio (R C-O ) of the peak area derived from the C-O bond defined in the present invention is the arithmetic mean value of the calculated values at 5 points on the measurement surface, as described above.
[0030] <[O-Si—O bond strength] / [C-Si—O bond strength]> Surface analysis by XPS was carried out in the same manner as described for the above-mentioned "<Ratio (R C-O ) of the peak area derived from the C-O bond>". For the Si2p spectrum in the range of 96 to 110 eV, the spectral components were separated by peak fitting, the peak area (A1) derived from the O-Si-O bond and the peak area (A2) derived from the C-Si-O bond were measured, and A1 / A2 was taken as [O-Si—O bond strength] / [C-Si—O bond strength]. The [O-Si—O bond strength] / [C-Si—O bond strength] defined in the present invention is the arithmetic mean value of the calculated values of [O-Si—O bond strength] / [C-Si—O bond strength] at 5 points on the measurement surface, as described above.
[0031] [Example 1] As a raw material for plasma polymerization, a mixture of 3-aminopropyltriethoxysilane and ethanol was used. Also, argon gas was used as the carrier gas. The temperature of the raw material and the carrier gas was controlled at 40°C. Using an apparatus with the same configuration as shown in FIG. 1, an alternating current with a frequency of 13.56 MHz and an output of 100 W was passed between the planar electrodes. With a decomposition reaction time of 20 milliseconds and a polymerization reaction time of 40 milliseconds, a coat layer containing a plasma polymer was formed on the surface (one side) of a copper foil (long side 400 mm × short side 300 mm × thickness 35 μm). Thus, the metal foil with a coat layer of Example 1 was obtained.
[0032] [Examples 2 to 5] In Example 1, except that the decomposition reaction time and the polymerization reaction time in plasma polymerization were changed, metal foils with coat layers of Examples 2 to 5 shown in the following table were obtained in the same manner as in Example 1.
[0033] [Examples 6 to 10] The metal foils with coating layers of Examples 6 to 10 shown in the table below were obtained in the same manner as in Example 1, except that in Example 1, a mixture of 3-methacryloxypropyltrimethoxysilane and 2,6-di-tert-butyl-p-cresol was used as the raw material and the decomposition reaction time and polymerization reaction time in the plasma polymerization were changed.
[0034] [Comparative Example 1] The above copper foil (long side 400 mm×short side 300 mm×thickness 35 μm) without any coating layer formed thereon was used as the metal foil of Comparative Example 1.
[0035] [Comparative Example 2] The metal foil with a coating layer of Comparative Example 2 shown in the table below was obtained in the same manner as in Example 1, except that a mixture of tetraethoxysilane and ethanol was used as the raw material and the decomposition reaction time and polymerization reaction time in the plasma polymerization were changed.
[0036] [Comparative Example 3] The metal foil with a coating layer of Comparative Example 3 shown in the table below was obtained in the same manner as in Example 1, except that in Example 1, octamethylcyclotetrasiloxane was used as the raw material and the decomposition reaction time and polymerization reaction time in the plasma polymerization were changed.
[0037] [Comparative Examples 4 to 6] The metal foils with coating layers of Comparative Examples 4 to 6 shown in the table below were obtained in the same manner as in Example 1, except that a mixture of 3-aminopropyltriethoxysilane and ethanol was used as the raw material and the decomposition reaction time and polymerization reaction time in the plasma polymerization were changed.
[0038] 2 shows an SEM image of the coating layer side surface of the coating layer-attached metal foil of Example 10 and an SEM image of the thickness direction cross section. From the SEM image of the thickness direction cross section, it can be seen that a layer that is clearly different from the metal foil is formed on the metal foil surface. Similar layers were also confirmed in Examples 1 to 9 and Comparative Examples 2 to 6.
[0039] [Test example] <Peel strength test> A normal peel test was carried out based on the method specified in JIS C 6481:1996. A resin substrate was bonded to the surface of the coating layer of the metal foil with the coating layer of Examples 1 to 10 and Comparative Examples 2 to 6 (pressed for 2 hours under conditions of a surface pressure of 2.9 MPa and 210°C), to obtain a laminate, which was used as a metal-clad laminate. A metal-clad laminate was also obtained in the same manner for the copper foil of Comparative Example 1. The resin substrate used was one in which two sheets of TU-933P+ (thickness 50 μm), a resin base material for printed wiring boards manufactured by TUC, were laminated together. Masking tape was applied to this metal-clad laminate, and copper chloride etching was performed, after which the masking tape was removed to produce a printed wiring board having a circuit wiring width of 10 mm. Test piece a used in this peel strength test and test piece b used in the heat resistance test described below were cut out from this wiring board. Next, at room temperature (25°C), the circuit wiring portion (copper foil portion) of test piece a was pulled at a speed of 50 mm / min in a 90 degree direction using a Tensilon tester manufactured by Toyo Seiki Seisakusho Co., Ltd. to peel it off from the resin substrate. The peel strength a (normal peel strength, kN / m) during this peeling was measured. This peel strength a is shown in the "Peel strength" column in the table below.
[0040] <Heat resistance (peel strength retention rate) test> Using the above test piece b, a peel strength test after heat treatment was carried out based on JIS C 6481: 1996. The details are described below. Test piece b was heated in a heating oven at 280°C for 5 minutes, and then naturally cooled to room temperature. Then, using a Tensilon tester manufactured by Toyo Seiki Seisakusho Co., Ltd., the 10 mm wide circuit wiring portion of test piece b was peeled from the resin substrate at a speed of 50 mm / min in a 90 degree direction to measure the peel strength b (kN / m). 100 x [peel strength b / peel strength a] is the peel strength retention rate (%), and is shown in the table below.
[0041] [Table 1]
[0042] As shown in the above table, in the analysis of the metal foil itself of Comparative Example 1 having no coating layer and the surface of the coating layer by XPS, the ratio of the peak area derived from the C-O bond to the total area of each peak derived from each bond detected at 280 to 292 eV in the C1s spectrum (R C-O The coated metal foils of Comparative Examples 3 to 6, in which the R ) was less than 10%, had poor adhesion strength to other members, or could not maintain adhesion when exposed to a severe high-temperature environment. C-O Similarly, the coated metal foil of Comparative Example 2, in which the adhesion strength was higher than that specified in the present invention, was poor with respect to the adhesive strength to other members and was unable to maintain an adhesive state in a severe high-temperature environment. In contrast, it was found that the coated metal foils of Examples 1 to 10, which satisfy the requirements of the present invention, have excellent adhesive strength with other members and can adequately maintain an adhesive state even in a severe high-temperature environment. Furthermore, the thickness of the coating layer is increased to 30 nm or more, the total atomic concentration of silicon, aluminum, titanium and sulfur in the coating layer is increased to 0.5 times or more the carbon atom concentration, and R C-O It was also shown that by increasing the [O-Si-O bond strength] / [C-Si-O bond strength] ratio to 10 or more, the peel strength retention rate can be increased to 70% or more.
[0043] Although the present invention has been described in conjunction with embodiments thereof, we do not intend to limit our invention to any of the details of the description unless specifically stated otherwise, and believe that the appended claims should be construed broadly without departing from the spirit and scope of the invention as set forth in the appended claims.
[0044] This application claims priority based on Japanese Patent Application No. 2023-127872, filed in Japan on August 4, 2023, the contents of which are incorporated herein by reference as part of the present specification. [Explanation of symbols]
[0045] 1 power supply 2 Matching Box 3 Raw material supply device 4 Planar electrode 5 Plasma (activation raw material, fragmentation raw material) CG Carrier Gas
Claims
1. A coated metal foil, The coating layer has a thickness of 5 to 1000 nm, and in a C1s spectrum by X-ray photoelectron spectroscopy, the ratio of a peak area derived from a C—O bond to a total area of peaks derived from each bond detected at 280 to 292 eV (R C-O ) is 10 to 50%.
2. 2. The metal foil with a coated layer according to claim 1, wherein the total atomic concentration (at %) of silicon, aluminum, titanium and sulfur in the coating layer is 0.5 times or more the atomic concentration (at %) of carbon atoms.
3. The coated metal foil according to claim 2 , wherein the coating layer has a silicon atom concentration of 8 at % or more.
4. 4. The metal foil with a coated layer according to claim 3, wherein the coating layer satisfies [O-Si-O bond strength] / [C-Si-O bond strength]≧1 in a Si2p spectrum by X-ray photoelectron spectroscopy.
5. The ratio (R C-O 5. The coated metal foil according to claim 4, wherein the content of the SiO 2 in the coating layer is 10 to 45%.
6. The coating layer has a thickness of 30 to 990 nm, and the ratio (R C-O 6. The metal foil with a coated layer according to claim 5, wherein the ratio of O—Si—O bond strength to C—Si—O bond strength is 13 to 30%, and 26≧[O—Si—O bond strength] / [C—Si—O bond strength]≧10 is satisfied.
7. The coated metal foil according to claim 6 , wherein the metal foil is a copper foil.
8. The coated metal foil of claim 6 , wherein the coating comprises a plasma polymer.
9. A metal-clad laminate obtained by laminating an insulating substrate and the coated metal foil according to any one of claims 1 to 8, with the coating layer of the coated metal foil facing the insulating substrate.
Citation Information
Patent Citations
Method of coating a substrate for adhesive bonding
US20090155604A1
Polymer substrate with hardcoat layer, and manufacturing method for same
WO2017051914A1
Polymer substrate with hard coat layer
WO2018181572A1
Method and apparatus for forming coatings
JP2004510571A
Surface-treated copper foil for printed-wiring board, copper plated laminate sheet for printed-wiring board, and printed-wiring board
JP2017106068A